2014
DOI: 10.1177/0960327114543936
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of signal transducer and activator of transcription 3 and apoptotic pathways by betaine attenuates isoproterenol-induced acute myocardial injury in rats

Abstract: The present study was designed to investigate the cardioprotective effects of betaine on acute myocardial ischemia induced experimentally in rats focusing on regulation of signal transducer and activator of transcription 3 (STAT3) and apoptotic pathways as the potential mechanism underlying the drug effect. Male Sprague Dawley rats were treated with betaine (100, 200, and 400 mg/kg) orally for 40 days. Acute myocardial ischemic injury was induced in rats by subcutaneous injection of isoproterenol (85 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…Betaine, one of the most important alkaloids isolated from Chinese wolfberry, possesses beneficial properties against inflammation, fibrosis, and oxidation [ 18 , 26 , 27 ]. This study is the first to demonstrate that intragastric administration of betaine exerted protective effects on MCT-induced PAH in rats.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Betaine, one of the most important alkaloids isolated from Chinese wolfberry, possesses beneficial properties against inflammation, fibrosis, and oxidation [ 18 , 26 , 27 ]. This study is the first to demonstrate that intragastric administration of betaine exerted protective effects on MCT-induced PAH in rats.…”
Section: Discussionmentioning
confidence: 99%
“…Betaine, a highly important alkaloid isolated from Chinese wolfberry, mainly exists in berries, leaves, and stems, and possesses various pharmacological activities, such as anti-inflammation, anti-fibrosis, and anti-oxidation [ 14 , 15 , 16 ]. Notably, a series of studies has found that betaine possesses outstanding anti-inflammatory abilities and exerts protective effects by suppressing the NF-κB signaling pathways; these activities include alleviating lipopolysaccharide-induced memory impairment, high-fat diet plus carbon tetrachloride-induced liver fibrosis, and isoproterenol-induced acute myocardial injury [ 17 , 18 , 19 , 20 , 21 ]. These results aroused our interest and suggested that betaine may be a potential drug for PAH.…”
Section: Introductionmentioning
confidence: 99%
“…The rats in the three ISO + groups were pretreated with propranolol or TMP, while the rats in the control and ISO groups were treated with equal volumes of normal saline. Afterwards, the rats in all four administration groups were subcutaneously injected with ISO (85 mg/kg) for two consecutive days [20]. Blood (3 ml) was collected from the abdominal aorta for serum enzyme assays.…”
Section: Methodsmentioning
confidence: 99%
“…As a multifunctional agent, betaine possesses various physiological activities that include anti-oxidation, anti-inflammation, and anti-fibrosis ( 26 28 ). Notably, one study found that betaine exerted an anti-angiogenic activity in vivo and in vitro through the suppression of nuclear factor-κ B (NF-κ B) and Akt activation ( 29 ), another study showed betaine attenuated isoproterenol-induced acute myocardial ischemia via the regulation of signal transducer and activator of transcription 3 and apoptotic pathways ( 30 ). However, our study pointed out that high betaine levels were associated with poor clinical outcomes in patients with PH.…”
Section: Discussionmentioning
confidence: 99%